2020
DOI: 10.1002/jbm.a.36926
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles of Ga‐substituted ε‐Fe2O3 for biomedical applications: Magnetic properties, transverse relaxivity, and effects of silica‐coated particles on cytoskeletal networks

Abstract: Magnetic nanoparticles of ε-Fe 1.76 Ga 0.24 O 3 with the volume-weighted mean size of 17 nm were prepared by thermal treatment of a mesoporous silica template impregnated with metal nitrates and were coated with silica shell of four different thicknesses in the range 6-24 nm. The bare particles exhibited higher magnetization than the undoped compound, 22.4 Am 2 kg −1 at 300 K, and were characterized by blocked state with the coercivity of 1.2 T at 300 K, being thus the very opposite of superparamagnetic iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, changes occurring in the cytoskeleton architecture and dynamics also play a significant role during the differentiation process, especially when they are associated with significant modifications to the cellular morphology [20][21][22]. Regarding the influence of magnetic cues on cellular behavior, there are numerous studies focusing on the reorganization of the cytoskeleton network and the effects on the focal adhesion complex or gap junctions [23][24][25]. It has been shown that a magnetic field and high concentrations of MNPs can lead to a decrease in proliferation and negatively affect FA and cytoskeleton components [26,27].…”
Section: Interactions With Magnetic Materials and Magnetic Fields Can...mentioning
confidence: 99%
“…Furthermore, changes occurring in the cytoskeleton architecture and dynamics also play a significant role during the differentiation process, especially when they are associated with significant modifications to the cellular morphology [20][21][22]. Regarding the influence of magnetic cues on cellular behavior, there are numerous studies focusing on the reorganization of the cytoskeleton network and the effects on the focal adhesion complex or gap junctions [23][24][25]. It has been shown that a magnetic field and high concentrations of MNPs can lead to a decrease in proliferation and negatively affect FA and cytoskeleton components [26,27].…”
Section: Interactions With Magnetic Materials and Magnetic Fields Can...mentioning
confidence: 99%
“…Soon after, Lo HM et al demonstrated that similar AuNP could disrupt platelet-derived growth factor (PDGF)-induced FAK phosphorylation, decreasing the vascular smooth muscle cell adhesion to a collagen I-rich ECM and inhibiting cell migration [144]. Recently, Královec K., et al observed that a novel type of complex nanoparticles, SiO 2 @Ga-substituted ε-Fe 2 O 3 , also induced FA shortening and a loss of stress fibers in human lung adenocarcinoma A549 [145]. Therefore, inorganic nanoparticles disturb fiber formation and stability at first glance, leading to an impaired cell migration.…”
Section: Inorganic Nanoparticles and Focal Adhesions Dynamicmentioning
confidence: 99%
“…Metastable ε-Fe2O3 has attracted attention in recent years because of its enormous coercive force value up to 20 kE at room temperature and its ability to absorb electromagnetic waves in the millimeter range [3][4]. All together this provides great potential for the applicability of ε-Fe2O3 for photocatalysis, gas sensors, magnetic/electrical tunable high-speed wireless communication devices and biomedical applications [5][6][7][8][9][10]. ε-Fe2O3 is not well suited for permanent magnet applications due to its low residual magnetization.…”
Section: Introductionmentioning
confidence: 99%